Large eddy simulations of 45° inclined dense jets - Jiang, Baoxin (2015)
Submerged inclined dense jets (negatively buoyant jets) occur in many engineering applications such as brine discharges from seawater desalination plants and de-cooling water discharges from liquefied natural gas plants, and their mixing behavior needs to be examined in details for the environmental impact analysis. In the present study, a detailed numerical investigation was performed using the large eddy simulation (LES) approach with both the Smagorinsky and Dynamic Smagorinsky sub-grid scale (SGS) models to simulate the characteristics of the inclined dense jet with 45° inclination. The numerical predictions included the jet trajectory, geometrical characteristics, jet spread and eddy structures. Experimental measurements were also obtained for the validation of the LES predictions, and data from existing studies in the literature were included for comparison. Overall, the LES predictions were able to reproduce the geometric characteristics of the inclined dense jet in a satisfactory manner in most aspects. The dilution was however generally underestimated, which was attributed primarily to the inability of the SGS models to reproduce the convective mixing induced by the buoyancy-induced instability using the adopted grid spacing in the bottom half of the inclined dense jet.